FORMULASI KEBIJAKAN PENYUSUNAN STRUKTUR ORGANISASI TATA KERJA STUDI KASUS PROVINSI RIAU 2014 - Amanda Olivia Aslim; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The background of this research by Government Regulation No. 41 of 2007 concerning the regional Organization, which as one element in the implementation of government performance in providing services and development in the region. So to make local government policy, legeslatif and society is an actor involved in each policy. So the results of this study that the actors involved in the preparation of Ranperda organizational structure and the local government of Riau province, the regional council and the people of Riau province, in this case represented by legislators who hold the mandate of the people of Riau province in making policy. Riau provincial government that are involved in the preparation of this SOTK Ranperda is Governor together Ortal Bureau, the Legal Bureau, and the regional work units concerned. Smentara it, from which the Council Special Committee of Parliament and its organizational structure and team of experts, and Factions in DPRD Riau Province. Ranperda maker SOTK interests in the preparation of Ranperda has involved all SKPD, and the House of Representatives strip is adjusted by Government Regulation No. 41 of 2007 to give according to their views on Ranperda SOTK. SOTK Ranperda manufacture does not involve the public directly of public policy. The interests of the Riau provincial government in policy formulation SOTK Riau Province is to formulate Ranperda SOTK, and conduct a hearing within the government, together with related SKPD. The interests of the Riau Provincial Parliament in lawmaking SOTK namely, providing views and proposals that are tailored to the needs of the Province and not in spite of PP No. 41 of 2007. The social base of the regulations SOTK course community and also SKPD in Riau province, so that the Government can give services more effectively and efficiently. This SOTK Bylaw provide relief workload for SKPD united as it has similarities duties so as to maximize the job. Furthermore, such relief can be felt by SKPD bloomed, because the workload SKPT. Keyword : policy formulation, organizational setructure, working procedures, Provinsi Riau